RISK FACTORS FOR SUDDEN DEATH AND PATHOMORFOLOGICAL CHANGES IN SUDDEN DEATH - Z.J. Narzilloeva (Western European Studies, 2024)
Risk factors for sudden death are diverse. These include high-grade ventricular extrasystole in patients with AMI, paroxysmal ventricular tachycardia, atrioventricular block and increased QT. As for risk factors, today it is possible to predict VCS with a certain degree of probability. Moreover, a correct forecast is possible by taking into account at least three factors - the degree of coronary insufficiency, a decrease in myocardial contractility, and rhythm disturbances.
Keywords: Ischemic heart disease; angina pectoris Prinzmetal; teleradiography